Up-regulation of microRNA-93 inhibits TGF-β1-induced EMT and renal fibrogenesis by down-regulation of Orai1 - Jifang Ma; Lei Zhang; Jianbing Hao; Naqi Li; Jie Tang; Lirong Hao (Elsevier, 2018)
TGF-β1-induced excessive deposition of ECM and EMT process of tubular epithelial cells play critical roles in the development and progression of fibrosis in diabetic nephropathy (DN). Orai1 has been demonstrated to be involved in TGF-β1-induced EMT via TGF-β/Smad3 pathway. We are aimed to explore the effects of miR-93 on TGF-β1-induced EMT process in HK2 cells. In this study, our data showed that miR-93 was dramatically decreased in renal tissues of patients with DN and TGF-β1-stimulated HK2 cells. Moreover, the decreased level of miR-93 was closely associated with the increased expression of Orai1. Overexpression of miR-93 decreased Orai1 expression, and then suppressed TGF-β1-mediated EMT and fibrogenesis. Next, we predicted that the Orai1 was a potential target gene of miR-93, and demonstrated that miR-93 could directly target Orai1. SiRNA targeting Orai1 was sufficient to suppress TGF-β1-induced EMT and fibrogenesis in HK2 cells. Furthermore, Overexpression of Orai1 partially reversed the protective effect of miR-93 overexpression on TGF-β1-mediated EMT and fibrogenesis in HK2 cells. Taken together, Orai1 and miR-93 significantly impact on the progression of TGF-β1-mediated EMT and fibrogenesis in HK2 cells, and they may represent novel targets for the prevention strategies of fibrosis in the context of DN. Keywords: Diabetic nephropathy, MicroRNA-93, Epithelial-mesenchymal transition, Renal fibrogenesis, Orai1